IMPLEMENTASI AUTHENTIC ASESSMENT PADA PENDIDIKAN VOKASI TEKNIK INFORMATIKA: IMPLEMENTASI AUTHENTIC ASESSMENT PADA PENDIDIKAN VOKASI TEKNIK INFORMATIKA - Raimon Efendi (Dharmas Education Journal (DE_Journal), 2020)
This research is motivated by the lack of competence of educators in implementing effective and meaningful assessments and in accordance with the development of 21st century learning. The purpose of this study was to determine the lecturers' understanding of authentic assessment, implementation and suitability of authentic assessment in computer network learning, perceptions of lecturers and students in carrying out authentic assessments, and lecturer obstacles in implementing authentic assessments in computer network learning in the informatics engineering study program. This research is descriptive research. This research includes population research with the subject of 6 lecturers of informatic engineering study program and 34 students taking computer network courses. Data were collected through questionnaires, interviews and document review. Data were analyzed using descriptive analysis. The results showed that; The knowledge and competence of lecturers is sufficient to make authentic assessments according to authentic assessment standards. Lecturers are able to prepare authentic assessment tools, and are able to use web-based authentic assessment media. The perceptions of lecturers and students towards authentic assessment in terms of planning, implementing techniques and instruments in assessing the three aspects of learning fall into the good category. Time limitations, number of components / criteria, lack of student motivation in innovative learning are still obstacles in the implementation of the assessment. Overall authentic assessment has been well implemented as an assessment innovation in 21st century education.